Right Ventricular Dominance Is Associated With Inferior Outcomes After the Extracardiac Fontan. Issue 4 (July 2019) - West, Caroline; Maul, Timothy; Feingold, Brian; Morell, Victor O.
Background: Investigations of ventricular dominance and outcomes after the Fontan procedure have shown conflicting results. This may be due to the inclusion of multiple modifications of the Fontan or the omission of recently identified complications of the procedure. We examined the association between right ventricular dominance (RVD) and morbidity/mortality in a contemporary cohort following the extracardiac (EC) Fontan. Methods: We studied all pediatric patients at our center who underwent a predominantly fenestrated EC Fontan from 2004 to 2016. Outcomes assessed were freedom from (1) Fontan failure (death, takedown, listing for transplantation) and (2) complication (arrhythmia requiring medication, postoperative pacemaker, or implantable cardioverter defibrillator requirement, stroke, thrombosis in the Fontan circuit, protein losing enteropathy, plastic bronchitis, New York Heart Association class >2). We defined the perioperative period as occurring before hospital discharge or within 30 days of the Fontan. Results: A total of 137 patients (median age: 34 months, 62% male, 60% RVD) underwent the EC Fontan. Median duration of follow-up was 5.8 years (interquartile range: 2.4-9.0). Freedom from any event was 82.5% (RVD = 77%, LVD = 91%, χ 2 (1) = 5.03, P = .025) and RVD was associated with reduced event-free survival (hazard ratio: 2.94, P = .02). No confounders were identified. In the perioperative period, RVD was associated with reduced complication-free survival ( P = .004). After this period, RVD was associated with reduced failure-free survival ( P = .003). Conclusions: In this contemporary, single-center cohort of EC Fontan patients, RVD was associated with inferior outcomes.